A study of gene mutations and how they relate to the different types of ichthyosis. (1st March 2020) - Simpson, J.K.; Martinez‐Queipo, M.; Onoufriadis, A.; Tso, S.; Glass, E.; Liu, L.; Higashino, T.; Scott, W.; Tierney, C.; Simpson, M.A.; Desomchoke, R.; Youssefian, L.; et al.
Summary: Ichthyosis is a disorder in which the skin is very thick and scaly. It is usually caused by a genetic mistake (mutation). "Autosomal recessive" ichthyosis occurs when parents who are healthy carriers both pass on a mutant gene to their child, so the child inherits a double dose of the mutation and cannot make normal skin. Scientists have already discovered mutations in 13 genes that cause ichthyosis. This study looks at whether the type of mutation (genotype) tells us anything about the type of ichthyosis (phenotype). The doctors examined 146 ichthyosis patients, average age 17 years, from 124 families, recruited from 13 English hospitals. They extracted DNA from blood or saliva. They found mutations in 83% of patients; the other 17% presumably have mutations not detectable by current techniques or in different genes. There were mutations in 10 different ichthyosis genes, mostly a gene called TGM1 . To some extent different genotypes corresponded to different phenotypes. TGM1 ichthyosis usually has large, brown scales while ALOX12B mutations cause fine white scaling. ABCA12 mutations cause more severe ichthyosis, including the very serious harlequin type with distorted fingers; by contrast patients with milder ichthyosis usually had TGM1 or ALOX12B mutations. Nearly half of the babies with ALOX12B mutations were born with the top of their ear folded over. Some TGM1 patients had abnormally red skin while others with exactly the same mutation did not. In conclusion, this large study provides a lot of new information about ichthyosis, but genotype only partly predicts phenotype. This is a summary of the study: Genotype–phenotype correlation in a large English cohort of patients with autosomal recessive ichthyosis